On Simplified Labor Relations Policy in the Wartime - Кучма, Ольга Леонідівна (Research and Educational Innovation Center of Social Transformations, 2022)
Social relations development, the pandemic and the war make it necessary to review and update the legislation all the time. But the legislative changes should facilitate establishment of the labor relations in the new context without compromising the balance of interests of the parties to the legal relations, and be in line with the legislative basis. The research is focused on the changes introduced to the labor laws and aimed at adoption of the simplified procedures governing labor relations in the time of war. The purpose of the article is legal assessment of the novelties in the labor legislation in the part of simplified labor relations. The research includes the method of scientific knowledge, the dialectical method, the comparative law method, the formal legal method, the rational criticism method. The conclusions are detailed below. The simplified labor relations policy allows the parties to the labor contract (the employer and the employee) to determine the labor relations at their own discretion and bypass the labor guarantees protecting the employee. Such changes as above-mentioned are unfavorable for the employee because the latter is the least protected participant of the labor relations, and the employer may pressurize the employee to accept the disadvantageous conditions. Hence, the simplified labor relations policy disrupts the balance in the employer-employee relations and may be unfavorable to the latter. In the time of war, the government adopted the special law governing labor relations that considers the interests of the employer amid the challenges faced by the small businesses in connection with the war. Therefore, it is not rational to adopt the simplified labor relations policy to support the employers in course of war. In addition, the employees, apart from the employers, also require the proper support in the wartime. Reduction of the labor guarantees provided to the employees due to adoption of the simplified labor relations policy is likely to exacerbate the crisis at the labor market because the employers are given additional possibilities to terminate the labor contract and more. The practical value of this article constitutes identification of a number of flaws in the legislative changes as well as suggestion of the ways to eliminate such flaws. Also, it is worth mentioning that simplified labor relations are not prescribed by the Constitution of Ukraine

У статті розглядаються зміни до Кодексу законів про працю України в частині запровадження спрощеного режиму регулювання трудових відносин. Наголошено, що спрощений режим регулювання трудових відносин передбачає можливість укладення по суті трудового контракту, сторони можуть на власний розсуд врегулювати істотні умови трудового договору, не враховуючи ряд гарантій, встановлених трудовим законодавством. Оскільки роботодавець є сильнішим учасником трудових відносин, то дискусійно стверджувати про доцільність для працівника як учасника трудових правовідносин договірного регулювання всіх умов трудового договору, оскільки це погіршить його становище порівняно з законодавством. Звернено увагу на невідповідність під час дії воєнного стану Конституції України положень, які регулюють питання робочого часу та часу відпочинку. Також вказано на недоречність внесення таких змін взагалі, з огляду на те, що на період дії воєнного стану прийнято спеціальний закон у сфері регулювання трудових відносин і якщо є потреба ще змінити трудове законодавство на період дії воєнного стану, то зміни слід вносити саме до спеціального закону.
Про спрощений режим трудових відносин у період дії воєнного стану
Keywords: спрощений режим регулювання трудових відносин; воєнний стан; робочий час; час відпочинку; конституційні; simplified labor relations policy; wartime; work time; leisure time; constitutionality